A co-evolving cultural cluster in the periphery: Film and TV production in Galway, Ireland. (September 2019) - Collins, Patrick; Power, Dominic
Abstract: In this paper we trace the co-evolution of a set of industries and supporting institutions in the Film and television (TV) industry in one of Europe's most peripheral regions. It is a comprehensive overview of the key stages of development, from inception to sustainability with key roles enacted by a diverse set of actors, from community activists to the current Irish President. This work contributes to the growing literature that is focussing attention on the growth of creative economy activity beyond the city. We pay particular attention to the role played by firms, institutions and geography and their co-evolution towards a cluster of cultural activity in Galway, Ireland. Highlights: Traces the co-evolution of a cluster of economic and cultural activity in Galway, Ireland. Tracking the evolution of the cluster over four decades from inception to sustainability. TV and film production employing over 600 people; independently producing and co-producing content internationally. Highlighting interventions from language movements to government policy to Hollywood producers in the clusters development.